KEMAJEMUKAN MASYARAKAT DUSUN SUSURU DESA KERTAJAYA KECAMATAN PANAWANGAN KABUPATEN CIAMIS SEBAGAI MODEL MASYARAKAT PANCASILA - Akhmad Satori (Jurnal Ilmu Politik dan Pemerintahan, 2011)
The purpose of this study is to investigate and reveal empirically social, cultural and social life religious, the process of acculturation, social processes (the social system/form of cultural interaction and process systems / customs), the transition process in understanding the diversity of the community, as well as affect the public another model of socio-cultural life and religious communities susuru hamlet. Based on research results seem that Hamlet community Susuru maintain the philosophy of "Unity in Diversity" and the values contained in Pancasila even though theoretically they do not understand it. Dusun community Susuru feel that although their different religions and beliefs but meraka still feel that the other is the brother of a nation and a homeland. So they are in public life show mutual respect, appreciate and cherish. Society does not consider Susuru Hamlet Hamlet Susuru society that believes differently as enemies who should be shunned. National values like that that make one of the Dusun community life Susuru maintain a safe, peaceful and serene in the absence of conflict that could tear their divided.